PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KOPI BLESSING SIDIKALANG - Padang, Redi Sihar; Saputra, Hendra (Growth, 2025)
This study examines the effect of price and promotion on purchasing decisions of Blessing Sidikalang coffee. The study was conducted in Sidikalang District, Dairi Regency, with a population of 2,390 buyers. The sampling technique used probability sampling, and the sample size was determined using the Slovin formula to obtain 100 respondents. Data collection was carried out through a questionnaire measured using a Likert scale, and the data were analyzed using multiple linear regression and hypothesis testing, including the t-test, F-test, and coefficient of determination (R²). Before analysis, the data were tested using validity, reliability, and classical assumption tests. Data processing was carried out using the SPSS for Windows version 30.0 program. The results of the partial hypothesis test showed that price and promotion had a positive and significant effect on purchasing decisions of Blessing Sidikalang coffee. In addition, the results of the study also showed that price and promotion simultaneously had a positive and significant effect on purchasing decisions. The coefficient of determination (R²) value of 0.800 indicates that 80.0% of the variation in purchasing decisions is explained by price and promotion, while the remaining 20.0% is influenced by other variables outside this study.